Quorum quenching effect and kinetics of active compound from S. aromaticum and C. cassia fused packaging films in shelf life of chicken meat. (May 2019) - Mohan, C. Chandra; Harini, K.; Sudharsan, K.; Krishnan, K. Radha; Sukumar, M.
Abstract: The aim of this work is to investigate the effect of active compound kinetics on biofilm inhibition and quorum quenching in chicken meat. The results showed that 20–40 g/100 mL of exopolysaccharide inhibition can be achieved through treatment of particle size reduced S. aromaticum and C. cassia in P. aeruginosa . Inhibition of AHL molecules in P. aeruginosa exhibits the quorum quenching potentials of particle size reduced S. aromaticum and C. cassia . Application of spice fused edible films over chicken meat was found to inhibit its microbiota, through diffusion of cinnamaldehyde and eugenol at the rate of 0.79 × 10 −15 ± 0.02 × 10 −15 and 0.75 × 10 −10 ± 0.03 × 10 −10 cm 2 /s, respectively. Antimicrobial and AHL inhibition capabilities of spices were found to be the major contributors for shelf life extension of chicken meat. Particle size reduced S. aromaticum and C. cassia was found to be effective in control of lipid and protein oxidation in chicken meat stored at 4 °C. Highlights: S. aromaticum and C. cassia exhibited biofilm inhibition potentials in P. aeruginosa. S. aromaticum and C. cassia also exhibited quorum quenching potential. Diffusion of active compounds increased the shelf life of chicken meat. MAP assisted edible film packaging was examined for its effect on chicken meat. S. aromaticum and C. cassia inhibited AHLs produced by chicken meat microbiota.